The Influence of Parental Leadership Styles on Children's Personality Development (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This paper examines how different parental leadership styles (e.g., authoritarian, authoritative, permissive) influence the personality development of children. The research will explore how parenting practices impact children's sense of self-confidence, independence, and social skills. The paper will contribute to a better understanding of the role parents play in shaping their children's personalities.